2004
DOI: 10.1016/j.amjhyper.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Ramipril in the treatment of hypertension and proteinuria in children with chronic kidney diseases

Abstract: Ramipril is an effective and safe drug in children with chronic kidney diseases associated with hypertension, proteinuria, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
3
28
0
2
Order By: Relevance
“…This effect has been attributed to the suppression of angiotensin, which is a potent pro-inflammatory mediator [42]. In addition, these drugs have been found to improve proteinuria in a number of kidney diseases, such as nephrotic syndrome and acute glomerulonephritis [23], which is an added advantage for their use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been attributed to the suppression of angiotensin, which is a potent pro-inflammatory mediator [42]. In addition, these drugs have been found to improve proteinuria in a number of kidney diseases, such as nephrotic syndrome and acute glomerulonephritis [23], which is an added advantage for their use.…”
Section: Discussionmentioning
confidence: 99%
“…This increased propensity has been attributed to many factors, such as activation of the renin-angiotensin-aldosterone system, fluid overload, and corticosteroid therapy [19]. Calcium channel blockers, such as nifedipine and amlodipine, and angiotensin converting enzyme inhibitors, such as ramipril and enalapril, are the most commonly prescribed drugs to treat hypertension in children with renal disease [21][22][23]. However, the effect of obesity on the pharmacological response of these drugs in children with renal disease has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…From a strict evidence-based medicine perspective, the trial was designed to compare blood pressure targets and all subjects received a fixed dose ACE inhibitor, so to conclude that proteinuria reduction (and ACE inhibitors) were responsible for better outcomes, this analysis would need to be adjusted for blood pressure achieved. Two additional small uncontrolled studies and one systematic review in children with CKD also showed reduction in hypertension and proteinuria, with agents blocking the renin-angiotensin system [39][40][41]. More importantly, while only a small study, one controlled trial, compared an ARB with a calcium channel blocker in children with CKD and found a similar reduction in blood pressure with both agents, but a greater reduction in proteinuria with the ARB [42].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 99%
“…Cuando se administra una dosis de 6 mg/m 2 /día, el fármaco reduce la PA media en 24 h, en particular en niños con HTA o proteinuria graves 110 . Asimismo, al administrar una dosis inferior de ramipril (2,5 mg/m 2 /día), se observó una reducción de la PA y la proteinuria en niños con HTA esencial e HTA renal e insuficiencia renal crónica 137 .…”
Section: Bloqueadores Betaadrenérgicosunclassified